2019
DOI: 10.1007/s42452-019-0477-5
|View full text |Cite
|
Sign up to set email alerts
|

Statistical optimization for determination of trace amounts of RDX in matrix of HMX using GC-ECD

Abstract: 1,3,5,7-Tetranitro-1,3,5,7-tetrazocane (HMX) is one of the most powerful military explosives that is produced by means of Bechmann method. Simultaneous, 1,3,5-rinitroperhydro-1,3,5-triazine (RDX) as a by-product is produced in this method that affect on the purity and sensitivity of HMX. Using a simple and fast technique is important for determination of trace amounts of RDX in the HMX matrix. The technique of gas chromatography-electron capture detector (GC-ECD) was proposed for these reasons. Because the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…There is no doubt that more attention should be shown on the applications of DoE on these aspects. Some examples of DoE techniques applied for the development of analysis method in GC, TLC, and HSCCC are listed in Table 4 [111][112][113][114][115][116][117][118][119][120][121].…”
Section: High-speed Countercurrent Chromatography (Hsccc)mentioning
confidence: 99%
“…There is no doubt that more attention should be shown on the applications of DoE on these aspects. Some examples of DoE techniques applied for the development of analysis method in GC, TLC, and HSCCC are listed in Table 4 [111][112][113][114][115][116][117][118][119][120][121].…”
Section: High-speed Countercurrent Chromatography (Hsccc)mentioning
confidence: 99%
“…On the other hand, the pollution of water and wastewater and finally soil is significant in the process of explosives production [1]. Various methods have been used to determine explosives purity and trace amounts in natural samples that can be referred to gas chromatography (GC) [2], mass spectroscopy (MS) [3], high-performance liquid chromatography (HPLC) [4], thin layer chromatography (TLC) [5], ion mobility spectrometer (IMS) [6], voltammetry [7], luminescence (photo and chemiluminescence), and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the high mechanical sensitivity of HMX, in order to improve its safety, HMX was often mixed with many cladding materials to promote the safety of explosives, and has been widely used in the field of mixed explosives or propellants. The literatures [19][20][21][22][23][24][25][26][27] explored the effects of RDX, TNT, aluminized hydrides, TKX-50, CL-20 and other substances on the thermal safety, isothermal kinetics, explosion performance, thermal decomposition mechanism, sensitivity and mechanical properties of HMX. It was found that the properties of HMX alteration significantly in their mixtures.…”
Section: Introductionmentioning
confidence: 99%